Decentralizaction in Bogotá from the constitution of 1991 (2013)
In spite of decentralization vocation to the Colombian Constitution of 1991, intended for the DC District, it has tended to distort this concept, since it has been marked by a number of characteristics of the concepts of centralization, decentralization and delegation; situation conducting the embodiment of the present investigation. From the mystery of what has been the evolution of the concept decentralization in Bogotá, from the order of the 1991 Constitution, we develop three stages beginning on the contextualizing of decentralization under the Organic Statute of Bogotá, Decree Law 1421, 1993, identifying so the intent of the component with the idea of decentralization in the Capital District, followed by the description of the organizational structure of Bogota, ending with a tour from the perspective of the past administrations and their policies on the subject and conclusions thereto.